The Role of Self-Regulated Learning and Collaboration Skills in Improving Students' Perceptions of English Listening - Hosam Alting; Wasim Alting; Mohamad Ilham Maulana (JEES: Journal of Education and Educational Sciences, 2025)
This study aims to determine the extent to which Self-Regulated Learning and Collaboration Skills play a role in improving students' perceptions of listening skills in English. The background of this study is based on the importance of listening skills as a major component in mastering English, as well as the need to understand the contribution of internal and social factors in shaping students' perceptions of the learning process. This study used a quantitative approach with an explanatory research method. Data were obtained through distributing questionnaires to junior high school students. The data analysis technique used is Multivariate Analysis of Variance (MANOVA), which allows testing the simultaneous influence of two independent variables on students' perception as the dependent variable. The results of the analysis show that both Self-Regulated Learning and Collaboration Skills have a significant influence on students' perceptions of listening skills, both individually and interactively. This finding confirms the importance of self-regulation in learning and cooperation in groups as determining factors in shaping positive perceptions of English listening learning. This research is expected to provide a basis for the development of learning strategies that are more responsive to student needs in mastering listening skills.